2018
DOI: 10.4314/ejhs.v28i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Level of faecal coliform contamination of drinking water sources and its associated risk factors in rural settings of north Gondar Zone, Ethiopia: a cross-sectional community based study

Abstract: BackgroundToday, close to a billion people mostl living in the developing world do not have access to safe and adequate water. Several studies in Ethiopia indicate that the majority of the drinking water sources had coliform count beyond the WHO standard. Therefore, Regular quality control mechanisms need to be in place. The objective of this study is therefore to determine the level of faecal coliform contamination of drinking water and its associated factors in North Gondar Zone, Ethiopia.MethodsA community-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…The majority of water sources, 49.7% were under medium risk level and 31% of water sources were under high-risk levels. This study finding is in agreement with studies conducted in North Gondar and Eastern Tigrai zone, Ethiopia by Getachew et al 20 and Gebrewahd et al 16 respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of water sources, 49.7% were under medium risk level and 31% of water sources were under high-risk levels. This study finding is in agreement with studies conducted in North Gondar and Eastern Tigrai zone, Ethiopia by Getachew et al 20 and Gebrewahd et al 16 respectively.…”
Section: Discussionsupporting
confidence: 93%
“…is finding is agreed with the sample from store at Farta woreda, which showed 100% household storage samples were contaminated with E. coli [14,20]; a similar study conducted at Ghana Temale Metropolis found that 83% of household samples were positive for E. coli [11], and this finding was in compliance with the study conducted at Kolladiba town of Ethiopia, which showed that 32.5% water samples from household storage containers were found to be positive for faecal coliforms [17]. Similarly, a study conducted in Bona woreda of southern Ethiopia and Jimma zone of southwest Ethiopia showed that majority of water samples taken from household storage containers were not in compliance with the WHO guideline value of 0 CFU/ 100 ml [12,21,22].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, this result was comparable with earlier studies done in different parts of Ethiopia (58%) (Usman et al, 2016), and (55%) (Asfaw et al, 2016). ; while it was higher than studies done in rural areas of North Gondar Zone, Ethiopia (56.5%) (Getachew et al, 2018), in rural parts of Ethiopia (58%) (Usman et al, 2017), households in Hyderabad, India (36%) (Eshcol et al, 2008), Uganda (Agensi et al, 2019). This difference could be due to variability in sociodemographic characteristics, study setting, sample size, and study period.…”
Section: Bacteriological Quality Of Drinking Watermentioning
confidence: 61%